PENGARUH PEMBERIAN KOMBINASI LUMPUR LAUT DAN PUPUK KANDANG SAPI TERHADAP KETERSEDIAAN HARA N, P, K DI LAHAN BEKAS TAMBANG BAUKSIT - Alsyahdani, Daeng; Suswati, Denah; Sulakhudin, Sulakhudin (Jurnal Sains Mahasiswa Pertanian, 2020)
Ultisols has an advanced degree of development, characterized by deep profil, increase of clay fraction along with the depth of soil, soil acidity, and low base saturation. Low pH, low nutrient elements such as nitrogen, phosphor, and potassium, low availability of organic carbon, Ca, Mg, Na, cation exchange capacity (CEC), base saturation are the characteristic of post bauxite mining land. The land that was formerly bauxite mining process by removing of a layer of top soil until the layer that contains the seeds of bauxite called post bauxite mining land. Coastal sediment is sediment which contains quite high micro nutrients with low CEC so by the addition of coastal sediment expected to increase base saturation and soil fertility. Cow manure is one of the alternative to improve the fertility of the soil. This study get analyzed by Complete Randomize Design (CRD) consisting of 4 treatments and 5 replications. A Treatment (control), B treatment (1.5 kg coastal sediment + 2.5 kg of manure), C treatment (2.4 kg coastal sediment + 4 kg of manure), the last D treatment (3.3 kg coastal sediment + manure). This research analyzed with the F test, if significant continued with Tukeyâ€™s Honestly Significant Difference (HSD) at the 5% level to obtain the difference between treatments. Based on the result, combination of Coastal sediment and cow manure from the C treatment (2.4 kg coastal sediment + 4 kg manure) able to increase pH of soil up to 6.68, which is the highest pH among the other treatments.Â Keywords : Ultisols, coastal sediment, cow manure, bauxite mining.